Comparison of Optimized Soft-Tissue Suppression Schemes for Ultra-short Echo Time (UTE) MRI - Li, Cheng (2011)
Ultra-short echo time (UTE) imaging with soft-tissue suppression reveals short-T(2) components (typically hundreds of microseconds to milliseconds) ordinarily not captured or obscured by long-T(2) tissue signals on the order of tens of milliseconds or longer. The technique therefore enables visualization and quantification of short-T(2) proton signals such as those in highly collagenated connective tissues. This work compares the performance of the three most commonly used long-T(2) suppression UTE sequences, i.e. echo subtraction (dual-echo UTE), saturation via dual-band saturation pulses (dual-band UTE), and inversion by adiabatic inversion pulses (IR-UTE) at 3T, via Bloch simulations and experimentally in vivo in the lower extremities of test subjects. For unbiased performance comparison, the acquisition parameters are optimized individually for each sequence to maximize short-T(2) SNR and CNR between short- and long-T(2) components. Results show excellent short-T(2) contrast is achieved with these optimized sequences. A combination of dual-band UTE with dual-echo UTE provides good short-T(2) SNR and CNR with less sensitivity to B(1) homogeneity. IR-UTE has the lowest short-T(2) SNR efficiency but provides highly uniform short-T(2) contrast and is well suited for imaging short-T(2) species with relatively short T(1) such as bone water.